An Evaluation of the 2009 Children’s Right to Free Compulsory Education Act - Pandey, Shashank; Bhardwaj, Peehu (Journal of Research in Vocational Education, 2024)
A historic piece of legislation, the Right of Children to Free and Compulsory Education Act 2009 (RTE Act), intends to give all children between the ages of six and fourteen free and compulsory schooling. Pertaining education to the individual from childhood is a age long practice. With the gradual growth of time the concept of education system changes through various phrases. The education is a vital weapon used to shape a nation’s destiny by assuring to live a quality life with respect and dignity. The education is a continuous process and dynamic in nature which starts from our birth and ends with our last breath. It is not just acquiring knowledge it’s about fostering wisdom, seeking truth and continuously expanding one’s understanding. Making education available to everyone, regardless of color, caste, creed, sex, or place of birth, was the dream of those who drafted the Constitution. A new Article 21-A, which recognizes education as a fundamental right of all citizens, was incorporated with the 86th Amendment in 2002. In line with this, the Right of Children to Free and Compulsory Education Act 2009 came into effect on April 1st, 2010. It is a milestone towards realizing the fundamental right to education enshrined in the Indian Constitution. This paper will critically examine the RTE Act highlighting its positive impacts and limitations.